2016
DOI: 10.1021/acs.jpcc.6b10289
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanisms of Methanol Oxidation to Methyl Formate on Vanadia–Titania and Vanadia–Titania–Sulfate Catalysts

Abstract: Density functional theory calculations were carried out using both cluster and slab models to investigate the catalytic reaction network and the effect of sulfate promoter on methanol selective oxidation using the V2O5/TiO2 catalyst. The hemiacetal mechanism was reaffirmed to be the most favorable reaction pathway for the formation of methyl formate (MF) by the prediction of another reaction pathway involving formic acid. Molecular oxygen was found to assist the desorption of the reaction products from the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 89 publications
1
16
1
Order By: Relevance
“…MPA here) is unlikely to play a major role under the alcohol solvent [29,48], which (namely pyruvic acid in this work) is indeed not observed in our case. Instead, the most likely pathway would probably proceed via first the formation of hemiacetal, and the subsequent oxidation to MPA, which is consistent with that proposed by the experimental and theoretical works based on the oxidative esterification of primary alcohols [29,[34][35][36]48]. Both of these two steps would take place rather rapidly, thus leaving the intermediates present with amounts below the detection limit during the entire reaction, which is also in agreement with the other's work involving PA and hemiacetal as the intermediates [29,48].…”
Section: Reaction Pathwayssupporting
confidence: 84%
See 2 more Smart Citations
“…MPA here) is unlikely to play a major role under the alcohol solvent [29,48], which (namely pyruvic acid in this work) is indeed not observed in our case. Instead, the most likely pathway would probably proceed via first the formation of hemiacetal, and the subsequent oxidation to MPA, which is consistent with that proposed by the experimental and theoretical works based on the oxidative esterification of primary alcohols [29,[34][35][36]48]. Both of these two steps would take place rather rapidly, thus leaving the intermediates present with amounts below the detection limit during the entire reaction, which is also in agreement with the other's work involving PA and hemiacetal as the intermediates [29,48].…”
Section: Reaction Pathwayssupporting
confidence: 84%
“…Instead, the amphoteric catalysts containing both basicity and proper acidity such as Au/ZrO2 [30], Au/ZnO [31], Au/β-Ga2O3 [32], and Au/Ga3Al3O9 [33] are more efficient for the overall oxidative esterification compared to the catalysts containing only basicity. This appears to be reasonable, as the favorable pathway is generally believed to proceed via the oxidation of primary alcohol to aldehyde, followed by the reaction with alcohol to form hemiacetal intermediate, which is then further oxidized to the corresponding ester [34][35][36]. It has been reported that the condensation of methanol and aldehyde to form hemiacetal has a low energy barrier in the presence of acid sites [35,36].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, methyl formate (MF), produced from methanol and containing a number of organic functional groups (aldehyde, ether, and methyl groups), has been considered as an important chemical intermediate and as environmentally benign chemicals in the emerging area of “green chemistry”. It is widely used in the chemical industry to produce dozens of chemicals and is exploited as an important precursor in the pharmaceutical and pesticide productions. Generally, MF is produced via the carbonylation and dehydrogenation reactions of methanol at a high temperature (>100 °C). These thermal synthetic methods suffer from medium conversion ( e.g ., <50%) and a large lack of product selectivity ( e.g .…”
Section: Introductionmentioning
confidence: 99%
“…Methyl formate (MF, HCOOCH 3 ) and dimethoxymethane (DMM, CH 3 OCH 2 OCH 3 ), produced from methanol, have been considered as significant organic processing intermediates in C 1 based chemistry and as environmentally benign chemicals in the emerging area of “green chemistry”. They are widely applied for the production of chemicals, such as formic acid and formamide [3,4] . Both the MF and DMM, containing several organic substituents (e. g., aldehyde, ester, ether, and methyl groups), also is used as important precursors to produce pharmaceuticals and pesticides and as an additive to petroleum [5] .…”
Section: Introductionmentioning
confidence: 99%